Ground-Level Geriatric Falls: A Not-So-Minor Mechanism of Injury. (6th November 2014) - Parker, Simon; Afsharpad, Arash
Abstract : Introduction . Ground-level falls are typically regarded as a minor mechanism of injury that do not necessitate trauma team activation; however, they represent a significant proportion of hospitalised trauma and can result in multisystem injury. Case Presentation . A 79-year-old nursing home resident was brought to the emergency department following an unwitnessed fall. She suffered dementia and had a seizure in the department resulting in a reduced GCS, making history and examination difficult. She was diagnosed with a right proximal humerus fracture and admitted under joint orthopedic and medical care. Following orthopedic review, further X-rays were requested which showed bilateral neck of femur fractures. The following day she had bilateral hip hemiarthroplasties and K-wire stabilisation of the right shoulder. Several days later, when cognition had improved, she was noted to be avoiding use of the left arm and was found to also have a left proximal humerus fracture which was managed conservatively. Conclusion . Trauma patients with reduced cognitive function should undergo full ATLS assessment, and a prospective trial is required to see if age should be incorporated as a criteria for trauma team activation. More liberal use of advanced imaging such as a full body CT-scan may be beneficial.